Estimativa da vulnerabilidade natural de aqüíferos: Uma contribuição a partir da resistividade e condutância longitudinal - Braga, Antonio Celso De Oliveira [UNESP] (My University, 2008)
This paper describes the results obtained with DC resistivity method using vertical electrical soundings (Schlumberger array), applied to environmental studies involving the groundwater. Aquifers natural vulnerability, important tool in environmental studies, can be estimate starting from geoelectrical methods, whose parameters resistivity and longitudinal conductance, allied to the type of aquifers occurrence (unconfined and confined aquifer) and water table depth, they allowed to obtain an index of corresponding natural vulnerability to the usually used. The results, applied in a preliminary phase of studies, are good, allowing a better direction and programming of the posterior phases. © 2008 Sociedade Brasileira de Geofísica.
Estimate of the aquifers natural vulnerability: A contribution from resistivity and longitudinal conductance
Keywords: Aquifer vulnerability; Longitudinal conductance; Resistivity